Nurses' sense of coherence and stress management strategies against the types of health status - Katarzyna Betke; Małgorzata Anna Basińska; Anna Andruszkiewicz (Wiley, 2021)
Abstract Aim The main objective of this paper was to establish types of health status in the group of practicing nurses. Design Positive psychology defines human health as the underlying resource for all life activities, including professional work. Practicing nurses are exposed to a variety of professional pressures, most notably high‐stress burden. Long‐term functioning in conditions of work‐related overburden and stress may compromise the health status of nurses and make them vulnerable to somatic or psychosomatic conditions. Methods In this study, we used original worksheets for collecting socio‐economic data and health‐related data, Orientation to Life Questionnaire (SOC‐29), General Health Questionnaire (GHQ‐28), Brief COPE Inventory (Mini‐COPE) and the somatic symptom scale. K‐means clustering analysis for cases was used to identify types of health status among the surveyed nurses. Results This survey discovered that specific types of health status can be distinguished among practicing nurses. The nurses represented various types of health status, levels of the sense of coherence and the use of stress management strategies.